Perinatal outcomes in dichorionic diamniotic twins with multifetal pregnancy reduction versus expectant management: A systematic review and meta-analysis. Issue 25 (19th June 2020) - Jin, Bihui; Huang, Qiongxiao; Ji, Mengxia; Yu, Zhizhi; Shu, Jing
Abstract: Background: Published findings on perinatal outcomes of multifetal pregnancy reduction (MPR) of dichorionic diamniotic (DCDA) twin pregnancy to singleton are controversial. We performed a meta-analysis to appraise the effects of MPR of DCDA twin pregnancy versus expectant management on perinatal outcomes. Methods: Four electronic databases were searched from their inception to June 15, 2019, to identify publications that appraised MPR before 15 weeks of gestation. Studies reporting perinatal outcomes of both MPR of DCDA twin pregnancy to singleton and expectant management were considered. The relative risks (RRs) and mean differences with 95% confidence intervals (CIs) were pooled using a random-effects model. Results: Six studies involving 7398 participants showed that MPR of DCDA twin pregnancy to singleton was associated with a lower risk of preterm birth (5 studies with 7297 participants; RR: 0.30, 95% CI: 0.22–0.40; P  < .001) and higher birth weight (4 studies with 5763 participants; mean differences: 548.10 g, 95% CI: 424.04–672.15; P  < .001) than expectant management; there was no difference in the occurrence of miscarriages (5 studies with 7355 participants; RR: 1.57, 95% CI: 0.90–2.75; P  = .11). Sensitivity analysis showed that all the results were stable and reliable, with the omission of 2 studies with serious risk of bias. Conclusion: Compared to expectant management, MPR of DCDA twin pregnancy to singleton prevents preterm birth and low birth weight, without increasing the risk of miscarriages. Regarding perinatal morbidity related to preterm birth, MPR can be reserved as a remediation measure to improve the perinatal outcomes of DCDA twin pregnancies. Abstract : Supplemental Digital Content is available in the text